Perceptions of climate change and climate change policies within the tourism sector in Mauritius. Issue 1 (2nd January 2022) - Dhoomun, Lovisha; Hytten, Karen F.; Perry, Paul
ABSTRACT: Tourism is the most important export-oriented economic activity in Mauritius. Climate change is predicted to exacerbate environmental degradation in coastal areas, where rapid tourism development is burdening the environmental attributes on which the island's tourism depends. This research examines climate change risk perceptions among key stakeholders within the tourism sector in Mauritius. It also explores their perceptions of the public policies which guide the management of climate change, their policy preferences and the perceived barriers to an effective approach. The stakeholders consider climate change as being potentially catastrophic and as representing significant risks for tourism. However, the majority lacked awareness of climate change policies as well as the importance of adaptation in Mauritius, and viewed the current institutional approach as being inadequate or insufficient. Therefore, there is an imperative need for improved communication among tourism stakeholders and information about adaptation needs to be disseminated through sources perceived as being credible.